Whole‐genome resequencing and transcriptome analysis provide insights on aphid‐resistant quantitative trait loci/genes in Sorghum bicolor. (11th June 2021) - Zhang, Jiwei; Li, Wanglong; Lv, Peng; Yang, Xin; Xu, Wang; Ni, Xianlin; Feng, Hui; Zhao, Ganlin; Pu, Mei; Zhou, Shixin; Zhao, Zhixue; Li, Ling; et al.
Abstract: The sorghum aphid ( Melanaphis sacchari ) has emerged as a serious pest for Sorghum bicolor and a major factor limiting its production worldwide. In this study, whole‐genome resequencing of resistant and susceptible bulks from a recombinant inbred line (RIL) population was conducted together with transcriptome analysis of the parent to identify genes underlying aphid resistance. In the NGS‐based bulked segregation analysis (BSA), using a total of 920, 389 genome‐wide high‐confidence markers, four QTLs, qtlMs‐6.1, qtlMs‐6.2, qtlMs‐6.3, and qtlMs‐6.4, were identified on chromosome 6. Based on comparative transcriptome analysis, 245 differentially expressed genes (DEGs, 190 upregulated and 55 downregulated) and 576 DEGs (336 upregulated and 240 downregulated) were identified at 4 dpi in 407B (resistant) and 7B (susceptible), respectively. The DEGs in 407B were enriched in 'DNA replication', 'flavone and flavonol biosynthesis' and 'flavonoid biosynthesis', which are associated with plant stress resistance. The QTL‐seq study identified a SNP marker (Chr6: 2686447C>G) that was validated on a diverse panel and could be used in molecular marker‐assisted selection to improve aphid resistance in sorghum.